Main systems development of K-band linac - Ayzatsky, M.I.; Biller, E.Z.; Dovbnya, A.N.; Kushnir, V.A.; Mitrochenko, V.V.; Perezhogin, S.A.; Khodak, I.V. (Вопросы атомной науки и техники, 1999)
The main purpose of our work is the creation of the small-sized linear electron accelerator on the energy up to 5 MeV on the base of such low-power Х- and K-bands sources. In this paper the results on development of main systems for such an accelerator are represented: two versions of an injector system and accelerating section. The operating frequency of the accelerator is 12500 MHz.